2012
DOI: 10.1101/lm.026674.112
|View full text |Cite
|
Sign up to set email alerts
|

d-cycloserine does not facilitate fear extinction by reducing conditioned stimulus processing or promoting conditioned inhibition to contextual cues

Abstract: The NMDA receptor partial agonist D-cycloserine (DCS) enhances the extinction of learned fear in rats and exposure therapy in humans with anxiety disorders. Despite these benefits, little is known about the mechanisms by which DCS promotes the loss of fear. The present study examined whether DCS augments extinction retention (1) through reductions in conditioned stimulus (CS) processing or (2) by promoting the development of conditioned inhibition to contextual cues. Rats administered DCS prior to extinction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Under this model, DCS enhances inhibitory learning to the context, but allows extinction to remain vulnerable to behavioral manipulations that affect the context memory, including the contextual renewal and reconditioning effects. In a direct test of the context inhibition idea, Baker et al (2012) found that DCS promoted extinction, but the extinction context could be conditioned just as readily as a control context; i.e., there was no evidence for a retardation of acquisition effect that is often used as evidence for inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Under this model, DCS enhances inhibitory learning to the context, but allows extinction to remain vulnerable to behavioral manipulations that affect the context memory, including the contextual renewal and reconditioning effects. In a direct test of the context inhibition idea, Baker et al (2012) found that DCS promoted extinction, but the extinction context could be conditioned just as readily as a control context; i.e., there was no evidence for a retardation of acquisition effect that is often used as evidence for inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…One such treatment is that of d-cycloserine (DCS), a glutamate receptor modulator, which has been shown to enhance long-term fear extinction in both adolescent and adult rats. 23,38 Comparable results have been shown with selective serotonin reuptake inhibitors, which, when administered chronically in combination with extinction training, prevent the return of fear memory in mice. 39,40 These results are promising, but nonpharmacological treatments may be optimal or preferred for treating the developing brain.…”
Section: Novel Mechanisms For Fear Reductionmentioning
confidence: 92%
“…As an example, pharmacological treatments have been shown to enhance fear regulation. One such treatment is that of d ‐cycloserine (DCS), a glutamate receptor modulator, which has been shown to enhance long‐term fear extinction in both adolescent and adult rats . Comparable results have been shown with selective serotonin reuptake inhibitors, which, when administered chronically in combination with extinction training, prevent the return of fear memory in mice .…”
Section: Novel Mechanisms For Fear Reductionmentioning
confidence: 99%
“…This leaves open the possibility for manipulations that facilitate extinction, for example, to do so by affecting the development of inhibition to context rather than what is assumed, namely, the development of inhibition to the CS or occasion setting to the context. In a recent study by Baker, McNally, and Richardson (2012), such a design was used and while d-cycloserine was shown to facilitate the extinction of conditioned freezing to a CS, this study went further than others by testing whether the extinction context had developed enhanced inhibitory learning in d-cycloserine-treated animals. The results, unfortunately, are somewhat equivocal on this point because although the extinction context in drug-treated animals was no slower than in controls at acquiring fear of its own, a more traditional summation test for conditioned inhibition was not performed.…”
Section: Psychological Considerations In the Study Of Extinctionmentioning
confidence: 99%